2018
DOI: 10.1101/lm.047555.118
|View full text |Cite
|
Sign up to set email alerts
|

Cued fear memory generalization increases over time

Abstract: Fear memory is a highly stable and durable form of memory, even over vast (remote) time frames. Nevertheless, some elements of fear memory can be forgotten, resulting in generalization. The purpose of this study is to determine how cued fear memory generalizes over time and measure underlying patterns of cortico-amygdala synaptic plasticity. We established generalization gradients at recent (1-d) and remote (30-d) retention intervals following auditory cued fear conditioning in adult male C57BL/6 mice. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 105 publications
7
43
0
1
Order By: Relevance
“…While samples sizes should be determined a priori using a statistical power analysis (e.g., G*Power, Univeritat Dusseldorf), we have found that 12-15 animals/group produces reliable measures (Pollack et al, 2018 The stimulus protocol is designed by the experimenter. For example, a stimulus protocol we have used for training in mice is: The subject freely explores the chamber for 3 min prior to the presentation of a 20-s, 5-kHz, 72-75 dB CS that co-terminates with a 0.5-s, 0.5-mA US.…”
Section: Day 0 (Habituation; Optional)mentioning
confidence: 98%
See 4 more Smart Citations
“…While samples sizes should be determined a priori using a statistical power analysis (e.g., G*Power, Univeritat Dusseldorf), we have found that 12-15 animals/group produces reliable measures (Pollack et al, 2018 The stimulus protocol is designed by the experimenter. For example, a stimulus protocol we have used for training in mice is: The subject freely explores the chamber for 3 min prior to the presentation of a 20-s, 5-kHz, 72-75 dB CS that co-terminates with a 0.5-s, 0.5-mA US.…”
Section: Day 0 (Habituation; Optional)mentioning
confidence: 98%
“…For instance, Pollack et al. () tested a set of tone frequencies (2 to 12 kHz) after training at 5 kHz in mice. Results revealed discrimination at 2, 3, and 12 kHz (recent) and generalization at 2 and 3 kHz (remote).…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations